2016
DOI: 10.1039/c6dt00969g
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing the dendritic growth of zinc in an ionic liquid containing cationic and anionic zinc complexes for battery applications

Abstract: Metallic zinc is a promising negative electrode for high energy rechargeable batteries due to its abundance, low-cost and non-toxic nature. However, the formation of dendritic zinc and low Columbic efficiency in aqueous alkaline solutions during charge/discharge processes remain a great challenge. Here we demonstrate that the dendritic growth of zinc can be effectively suppressed in an ionic liquid electrolyte containing highly concentrated cationic and anionic zinc complexes obtained by dissolving zinc oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 60 publications
1
54
0
Order By: Relevance
“…Aqueous Zn–Ni, Zn–polymer, Zn–air, and Zn–ion batteries are reported . The commercialization prospects of secondary Zn‐based batteries are still elusive because of a severe problem: dendrite formation on the Zn anode after successive charge–discharge cycles . Furthermore, the corrosion and hydrogen gas evolution on the Zn anode are major side reactions …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Aqueous Zn–Ni, Zn–polymer, Zn–air, and Zn–ion batteries are reported . The commercialization prospects of secondary Zn‐based batteries are still elusive because of a severe problem: dendrite formation on the Zn anode after successive charge–discharge cycles . Furthermore, the corrosion and hydrogen gas evolution on the Zn anode are major side reactions …”
Section: Introductionmentioning
confidence: 99%
“…Dendrite formation on the Zn electrode is a natural but complicated problem . When the Zn battery is working, Zn is stripped off the surface to create Zn 2+ under battery discharge, and the Zn 2+ deposits on Zn under battery charge.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature studies have shown several approaches to improving the performance of metal-air batteries such as suppressing zinc dendrite growth in an ionic liquid electrolyte containing highly concentrated cationic and anionic zinc complexes [15] and the use of Co3O4 nanoparticles that were synthesized on N-doped Vulcan carbon as a hybrid bifunctional electrolcatalyst [16]. Another approach with a particular focus on the anode focused on the production of the electrode as foam [17] or fibrous [18] materials to improve life cycle and energy density.…”
Section: Introductionmentioning
confidence: 99%